The evaluation of amine-functionalized iron oxide Nnanoparticles as potential dye removal from aqueous medium - Khairil Azizi, Azra Filzaira; Che Nan, Siti Nursyamsulbahria; Mohd Salim, Rosliza; Abd Hamid, Shafida; Razali, Azaima (2022)
Magnetic nanoparticles (MNP) are superparamagnetic nanoparticles that are gaining significant interests due to their high surface-to-volume ratio and unique physicochemical properties. However, anisotropic dipolar attraction may cause the MNP to aggregate and undergo biodegradation when their surfaces are exposed directly to biological environment MNP (Souza et al., 2013)⁠⁠. This can be overcome by encapsulating the MNP with biocompatible and stabilizer shell using polymers or inorganic compounds (Mourdikoudis et al., 2021)⁠⁠.